Morphological and structural investigations of Egyptian water buffalo (Bubalus Bubalis) sertoli cells - Rutland, Catrin S.; Derbalah, Amira; Karam Roshdy, Karam; El-Gendy, Samir (Lifescience Global, 2017)
Buffaloes are essential part of the economy in many countries and provide sustainable food in addition to being working animals. Inefficiency in reproduction has become problematic in recent years due to a number of factors and although much research concentrates on the female, very little is known about the male buffalo reproductive system. To address this deficiency in the literature, testes were obtained from 20 clinically healthy water buffalo (Bubalus Bubalis) bulls aged 3 years old. Scanning electron microscopy showed that the Sertoli cells were columnar to triangle shaped with many processes. In the middle portion of the seminiferous tubules, the Sertoli cell had two types of processes with sheet like and slender cord like appearances. The sheet like processes had simple smooth margins originating from Sertoli cells, surrounding the surfaces of spermatogonia and spermatocytes. The slender cord like processes formed networks around other spermatogenic cells. Transmission electron microscopy showed that the Sertoli cells contained a large irregular shaped nucleus with deep nuclear membrane indentations, few mitochondria, aggregates of ribosomes and few rough endoplasmic reticulum which were observed within the indentations. Each nucleus contained a multivesicular nuclear body, containing vesicles, tubules and ribosome like dense structures. The work herein describes the structure and location of key reproductive cells within the water buffalo. Understanding the features of the male reproductive system is essential in order to advance studies into the reproductive decline of this species and the Bovidae family.